A Topical Revelation of the Repressed Structure of Schoenberg’s 'Pelleas und Melisande" - Hood, Danielle (Res Facta Nova, 2025)
The question of the form of Pelleas und Melisande is a vexed one, and has been so since Berg’s 1920 Kurze Thematische Analyse. Berg described it as ‘[n]ever […] purely descriptive’ but against popular viewpoints claimed it is in symphonic form. Derrick Puffett attributed this stance to Berg’s ‘clear historicist agenda’ to ‘reaffirm the traditionalism at the heart of the Second Viennese School’s view of itself ’. In the minds of contemporary scholars, the attested ‘purity’ of the sonata form could not be associated with this ‘inferior’ programme music. This article describes the interaction between the two aspects—programme and form—focussing in particular upon the way in which this interaction simultaneously appears to refuse sonata form, in a manner seemingly analogous to Freudian repression, while also staging the sonata cycle through the deployment of a topical narrative. This description is intimately informed by conceptions of multivalence, as theorised in musical terms by James Webster but, perhaps more importantly here, in more general semiotic terms by Barthes. Finally, through mapping the topical reading onto Vande Moortele’s taxonomic system and his analysis of the piece the hidden agendas of the repressed form are exposed in a work known for its thematic and formal uncertainty.